2018
DOI: 10.5830/cvja-2017-054
|View full text |Cite
|
Sign up to set email alerts
|

Participation in research improves overall patient management: insights from the Global Rheumatic Heart Disease registry (REMEDY)

Abstract: SummaryBackgroundRheumatic heart disease (RHD) is a major public health problem in low– and middle–income countries (LMICs), with a paucity of high–quality trial data to improve patient outcomes. Investigators felt that involvement in a recent large, observational RHD study impacted positively on their practice, but this was poorly defined.AimThe purpose of this study was to document the experience of investigators and research team members from LMICs who participated in a prospective, multi–centre study, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The present finding was also consistent with other studies conducted in Africa: Uganda, 56,57 Malawi 58 , Tanzania, 59 and South Africa. 60 In this study, the commonest reasons reported for missing monthly benzathine prophylaxis injections was long distance from hospitals (56.9%), lack of money (38%), unaffordability (30.8%), and inconvenient work schedule (22.5%). This finding is also supported by different studies.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…The present finding was also consistent with other studies conducted in Africa: Uganda, 56,57 Malawi 58 , Tanzania, 59 and South Africa. 60 In this study, the commonest reasons reported for missing monthly benzathine prophylaxis injections was long distance from hospitals (56.9%), lack of money (38%), unaffordability (30.8%), and inconvenient work schedule (22.5%). This finding is also supported by different studies.…”
mentioning
confidence: 65%
“…The present finding was also consistent with other studies conducted in Africa: Uganda, 56 , 57 Malawi 58 , Tanzania, 59 and South Africa. 60 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the experience of research team members from UEM teaching hospital that was the core part of our program was evaluated through an online survey complemented with telephone interviews to gather additional qualitative data, demonstrating that participation in clinical research has a positive impact on patient management. 49 Furthermore, we have developed sustainable strategies and a network of national and international academic institutions working together on multiple common goals (UniLúrio, UEM, UPM, UniZambeze, UCSD, UNL-IHMT, Oporto University, Universidad de Granada, Universidade do Aveiro, Universidade Técnica de Lisboa, Universidade Federal de Minas Gerais). We have followed other initiatives which were successful such as the Better Health Information for Better Health Policy (INDEPTH) network, Consortium for Health Systems Policy Analysis in Africa (CHEPSAA), the partnership between Makerere University and Karolinska Institutet, the African/Asian Regional Capacity Development and RAHI-SATHI Indo-US are underway elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although there is an opportunity for local research teams to positively impact maternal sepsis management, challenges regarding institutional management and resource allocation, may hinder such improvement [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that participation in a large multi-country study, like the Global Maternal Sepsis Study (GLOSS), [ 9 ] can potentially improve clinical management of patients [ 10 ] and enhance local research capacity. While GLOSS was not designed to intentionally build the capacities of local researchers, some specific activities (Additional file 1 ) allowed for capacity strengthening.…”
Section: Introductionmentioning
confidence: 99%